Analysis of the Implementation of Good Manufacturing Practice (GMP) and Sanitation Standard Operating Procedure (SSOP) in the Processing of Cuttlefish (Sepia sp.) Fillets: Analisis Penerapan Good Manufacturing Pratice (GMP) dan Sanitation Standard Operating Procedure (SSOP) pada Proses Pengolahan Sotong (Sepia sp.) Fillet - Listyaningrum, Niken Prawesti; Hamida, Jurnaliza; Rumiyati, Sri (jurnal makanan tropis dan teknologi agroindustri, 2025)
The increasing production of cuttlefish in Indonesia has driven the demand for quality assurance and food safety, particularly in the form of frozen fillets. This study aims to analyze the implementation of Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP) in the processing of cuttlefish (Sepia sp.) fillets at PT XYZ, Pati Regency, Central Java. The research was conducted using a descriptive method through direct observation, interviews with relevant personnel, and documentation of production activities. The results showed that the company consistently applies GMP and SSOP principles from raw material reception to final product distribution. Sanitation procedures are strictly enforced, including the use of standardized chemicals, pest control, and regular employee training. Moreover, the company utilizes modern freezing technology such as Contact Plate Freezer (CPF) to maintain product quality and extend shelf life. The implementation of GMP and SSOP has proven effective in ensuring the hygiene, quality, and safety of the processed cuttlefish fillets.